Differential scanning calorimetry study of constrained groove pressed low carbon steel: recovery, recrystallisation and ferrite to austenite phase transformation. (July 2014) - Khodabakhshi, F.; Kazeminezhad, M.
Abstract : Low carbon steel sheets are subjected to severe plastic deformation (SPD) via constrained groove pressing (CGP) up to five passes. As a result of this process, strain magnitude up to 5·8 is imposed to the sheets, which leads to grain size of 225 nm. These nanostructured steel sheets, due to their high dislocation density and ultrafine microstructure, are very sensitive to heating. In the present study, recovery, recrystallisation and ferrite to austenite phase transformation phenomena for the SPD steel are investigated using differential scanning calorimetry method. The results show that with increasing the strain in steel sheets, the deformed stored energy (released through recovery and recrystallisation) and enthalpy of ferrite to austenite phase transformation are significantly increased and varied in 38·5–85·8 and 109–156·1 MJ m −3 ranges respectively. In addition, transformation temperature is decreased from 761 to 750°C after five CGP passes. However, recovery stored energy, recovery and recrystallisation peak temperatures are not changed, considerably. Experimental data show that with increasing the hardness, the stored energy is increased. One empirical equation is developed for relationship between hardness and stored energy of severely deformed low carbon steel. In addition, using the dislocation model, this mentioned relationship is justified.